The severity of essential hypertension in terms of blood pressure values does not depend on NOS3 (rs2070744) and GNB3 (rs5443) genes polymorphisms in the West-Ukrainian population - Sydorchuk, Andrii; Sydorchuk, Larysa (Journal of Education, Health and Sport, 2021)
Objective: to evaluate the association of essential arterial hypertension (EAH) and its severity with genes polymorphism of NOS3 (rs2070744) and GNB3 (rs5443) in West-Ukrainian population. Materials and methods. One-hundred EAH patients (48 – healthy control) participated in the cohort case-control study. Blood pressure (BP), Creatinine, glucose, lipids panel were studied. GNB3 (rs5443) and NOS3 (rs2070744) genotyping performed by TaqMan probes (CFX96™Real-Time PCR). Risk assessed by Relative Risk, Odds Ratio and 95% Confidential intervals. Results. A mutation of the NOS3 gene (786T>C, rs2070744) and the GNB3 gene (825C>T, rs5443) in the homozygous state in the West-Ukrainian population suffers from EAH occurs with a frequency of 16.67% and 8.33%, with no differences with the control subjects (p>0.05). In both groups dominate the T-allele of the NOS3 gene and the C-allele of the GNB3 gene: in patients by 12.5% ​​(c2=4.50; p=0.034) and 41.66% (c2=50.0; p<0.001), in the control – by 25.0% (c2=12.0; p<0.001) and 40.0% (c2=33.33; p<0.001), respectively. The results of the binary logistic regression analysis did not confirm the prediction of the EAH appearance by polymorphic variants of the NOS3 (rs2070744) and GNB3 (rs5443) genes. However, the TT genotype of the GNB3 gene (rs5443) increases unreliably the EAH risk almost twice as likely [OR=2.0; OR 95%CI:0.40-10.82; p>0.05]. Epidemiological analysis did not confirm the association of the NOS3 gene with the EAH severity. But T-allele of the GNB3 gene increases the probability of high normal BP almost 5 times [OR=4.86; OR 95%CI:0.99-24.75; p=0.042]. Conclusions: NOS3 (rs2070744) and GNB3 (rs5443) genes polymorphisms are not associated with blood pressure values and EAH severity as well.